Growing fear of Islamisation: representation of online media in Malaysia - Wan Mohd Nor, Murni; Gale, Peter (Taylor and Francis, 2021)
The use of hate speech in Malaysia has increased with access to the new media. Facebook, Twitter and the comments sections of news portals have been misused for distributing hateful content. This has heightened tensions among Malaysians. Violent incidences have occurred, such as church burnings, desecration of religious symbols and places of worship such as mosques. Some are of the opinion that intolerance contributes to such hostilities. However, the discourse surrounding intolerance is focused on Muslims and Islam, which adds to the growing fear of “strict Islam” amongst Malaysians. Sensationalised media reports on the issue of “creeping Islamisation” may widen the division between ethnicities. This study explores how popular Malaysian news portals represent Islamisation by using content and critical discourse analysis. Findings show that Islamisation tends to be framed negatively, contributing to the fear of Islamisation and restriction of fundamental freedoms.